2018
DOI: 10.1017/s1751731117003160
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pre-weaning feeding policies and other risk factors influencing growth rates in calves on 11 commercial dairy farms

Abstract: Growth rates in pre-weaned calves influence their health, age at first calving and lifetime productivity. Many farms restrict milk rations to encourage solid feed intake and facilitate early weaning, but this can compromise growth. This study determined the milk feeding policies and associated growth rates on 11 commercial dairy farms in South East England, each following their normal management regime. Between 26 and 54 heifers were recruited per farm, providing a final cohort of 492, of which 71% were pure H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 40 publications
3
40
0
1
Order By: Relevance
“…We also observed a negative association of feeding a diet consisting of at least 90% saleable milk for at least 7 d at time of farm visit with BRD versus any other milk diet, including waste milk or milk replacer. Several studies have evaluated the effect of milk intake volume on calf performance (Jasper and Weary, 2002;Johnson et al, 2017). Studies evaluating the amounts of milk fed to calves on health outcomes have found mixed effects.…”
Section: Feedmentioning
confidence: 99%
“…We also observed a negative association of feeding a diet consisting of at least 90% saleable milk for at least 7 d at time of farm visit with BRD versus any other milk diet, including waste milk or milk replacer. Several studies have evaluated the effect of milk intake volume on calf performance (Jasper and Weary, 2002;Johnson et al, 2017). Studies evaluating the amounts of milk fed to calves on health outcomes have found mixed effects.…”
Section: Feedmentioning
confidence: 99%
“…In order to reach future production targets, an average ADG of 0.70-0.80 kg/day for calves has been recommended. 8,35,36 The literature has previously been based on the US and European calf data and various growth rates have been cited in the literature ranging from 0.44 to 1.40 kg/day. 1,7,20 These growth rates varied depending on nutritional factors 7,27 and disease incidence.…”
Section: Discussionmentioning
confidence: 99%
“…11 A study by Johnson et al described how feeding policies and other risk factors impacted the growth rate on 492 UK calves. 36 The study reported that ADG varied between farms from 0.52 to 0.75 kg/day depending on how much milk was fed, the presence of for the fortnight prior to disease event, 1 level for the fortnight of the confirmed disease event, levels 2-4 are for the three fortnights (maximum number of fortnights until weaning assuming a calf was observed with an even on the first fortnight) after disease event fortnight. c Calves with diarrohea (n = 8) and soft faeces (n = 8) were included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiology studies in various countries around the world have determined that up to 46% of calves contract BRD [70,71]. For the calves that survive, there is mounting evidence of longer term consequences of juvenile disease on adult performance [72,73].…”
Section: Bovine Herpesvirus-1mentioning
confidence: 99%
“…For the calves that survive, there is mounting evidence of longer term consequences of juvenile disease on adult performance [72,73]. BRD-affected animals have reduced growth rates [71,74], which in turn delay the age at first breeding and first calving. This is often associated with bronchopneumonic lesions and pleural adhesions [75].…”
Section: Bovine Herpesvirus-1mentioning
confidence: 99%